Metformin effects on brain development following cranial irradiation in a mouse model. Issue 9 (27th May 2021) - Yuen, Nili; Szulc-Lerch, Kamila U; Li, Yu-Qing; Morshead, Cindi M; Mabbott, Donald J; Wong, C Shun; Nieman, Brian J
Abstract: Background: Cranial radiation therapy (CRT) is a mainstay of treatment for malignant pediatric brain tumors and high-risk leukemia. Although CRT improves survival, it has been shown to disrupt normal brain development and result in cognitive impairments in cancer survivors. Animal studies suggest that there is potential to promote brain recovery after injury using metformin. Our aim was to evaluate whether metformin can restore brain volume outcomes in a mouse model of CRT. Methods: C57BL/6J mice were irradiated with a whole-brain radiation dose of 7 Gy during infancy. Two weeks of metformin treatment started either on the day of or 3 days after irradiation. In vivo magnetic resonance imaging was performed prior to irradiation and at 3 subsequent time points to evaluate the effects of radiation and metformin on brain development. Results: Widespread volume loss in the irradiated brain appeared within 1 week of irradiation with limited subsequent recovery in volume outcomes. In many structures, metformin administration starting on the day of irradiation exacerbated radiation-induced injury, particularly in male mice. Metformin treatment starting 3 days after irradiation improved brain volume outcomes in subcortical regions, the olfactory bulbs, and structures of the brainstem and cerebellum. Conclusions: Our results show that metformin treatment has the potential to improve neuroanatomical outcomes after CRT. However, both timing of metformin administration and subject sex affect structure outcomes, and metformin may also be deleterious. Our results highlight important considerations in determining the potential benefits of metformin treatment after CRT and emphasize the need for caution in repurposing metformin in clinical studies.